Wybrane elementy koncepcji controllingu właścicielskiego w spółce z udziałem jednostek samorządu terytorialnego - Tendaj-Bielawska, Monika (Selected Elements of the Conception of Owner's Controlling in a Company with the Participation of Local Government Units, 2007)
The efficient and effective cooperation and the flow of governance and control information between corporate organs are of great importance for the good corporate governance process which a local government keeps. Hence using controlling conception for organizing an information flow about corporate function is intentional and useful.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 494-499